2000
DOI: 10.15760/etd.654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HRU Size on PRMS Performance in 30 Western U.S. Basins

Abstract: Semi-distributed hydrological models are often used for streamflow forecasting, hydrological climate change impact assessments, and other applications. In such models, basins are broken up into hydrologic response units (HRUs), which are assumed to have a relatively homogenous response to precipitation. HRUs are delineated in a variety of ways, and the procedure used may impact model performance. HRU delineation procedures have been researched, but it is still not clear how important these subdivision schemes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…A recent study has indicated that the size and subdivision of HRU does not significantly impact PRMS model performance [45]. The geographic PRMS parameters at each HRU were estimated from Geographic Information System (GIS) datasets including digital elevation models (DEM), soil maps, and land cover maps obtained online [28].…”
Section: Hydrological Modeling Frameworkmentioning
confidence: 99%
“…A recent study has indicated that the size and subdivision of HRU does not significantly impact PRMS model performance [45]. The geographic PRMS parameters at each HRU were estimated from Geographic Information System (GIS) datasets including digital elevation models (DEM), soil maps, and land cover maps obtained online [28].…”
Section: Hydrological Modeling Frameworkmentioning
confidence: 99%
“…Το συγκεκριμένο μοντέλο είναι ένα φυσικής βάσης, προσδιοριστικό, πλήρως κατανεμημένο μοντέλο συνεχούς χρόνου και αποτελεί ένα εργαλείο οικο-υδρολογικής προσομοίωσης, το οποίο έχει αναπτυχθεί για τις συνθήκες των ΗΠΑ, όπου και έχει εφαρμοστεί ευρέως ( Van Liew & Garbrecht, 2003;Chaubey et al, 2005;Jha, 2011;Steele, 2013) ( Kim & Kaluarachchi, 2009;Easton et al, 2010) έως μεσαίας και μικρής κλίμακας ( Feyereisen et al, 2007;Zhu et al, 2012;Bem Othman & Gueddari, 2014;Epelde et al, 2015). Επίσης, έχει εφαρμοστεί σε ποικίλες κατηγορίες κλίματος όπως σε λεκάνη απορροής αλπικού κλίματος στην Ελβετία , εύκρατου κλίματος στην Αγγλία (Whitehead, 2006;Glavan et al, 2011), στη Γαλλία (Pushpalatha, 2013), στις ΗΠΑ (Spruill et al, 2000), ημίξηρου κλίματος (Mosbahi et al, 2011), ξηρού (Al Mulla, 2005 και τροπικού (Alansi et al, 2009).…”
Section: περιγραφή μοντέλου Swatunclassified